2013
DOI: 10.1371/journal.pone.0056119
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Mapping Angiotensin-Converting Enzyme Gene: Separate QTLs Identified for Hypertension and for ACE Activity

Abstract: Angiotensin-converting enzyme (ACE) has been implicated in multiple biological system, particularly cardiovascular diseases. However, findings associating ACE insertion/deletion polymorphism with hypertension or other related traits are inconsistent. Therefore, in a two-stage approach, we aimed to fine-map ACE in order to narrow-down the function-specific locations. We genotyped 31 single nucleotide polymorphisms (SNPs) of ACE from 1168 individuals from 305 young-onset (age ≤40) hypertension pedigrees, and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
(38 reference statements)
2
24
0
Order By: Relevance
“…ACE and ACE2, are considered as regulators of blood pressure; thus, to study the polymorphisms in these genes is demanding from the view of understanding of the pathophysiology of hypertension. The insertion/deletion (I/D) polymorphism of the ACE gene (mapped on chromosome 17q23) and single nucleotide polymorphism G8790A of the ACE2 gene (mapped on chromosome Xp22) were found to be main pre-dispositions for systemic arterial hypertension (Chung et al 2013). A co-regulatory function between ACE and ACE2 was found in the case of vasoconstriction and vasodilatation that proceeds in the heart and kidney while in the kidney, levels of the ACE2 protein decrease in experimental animals with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…ACE and ACE2, are considered as regulators of blood pressure; thus, to study the polymorphisms in these genes is demanding from the view of understanding of the pathophysiology of hypertension. The insertion/deletion (I/D) polymorphism of the ACE gene (mapped on chromosome 17q23) and single nucleotide polymorphism G8790A of the ACE2 gene (mapped on chromosome Xp22) were found to be main pre-dispositions for systemic arterial hypertension (Chung et al 2013). A co-regulatory function between ACE and ACE2 was found in the case of vasoconstriction and vasodilatation that proceeds in the heart and kidney while in the kidney, levels of the ACE2 protein decrease in experimental animals with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, all these seven SNPs were strongly associated with latelife depression. By measured haplotype method, a study has suggested that functional polymorphisms within ACE gene could be located in a primary region from exon 13 (rs4316) to intron 18 (rs4344) including I/D polymorphism, which is responsible for decreased ACE activity (Chung et al, 2013). Additionally, three SNPs in the ACE gene in strong LD with each other (rs4333, rs4329, and rs4461142) were also significant in a large sample with major depressive disorder (Bosker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lymphoid forms of leukemia are CD68 negative [22]. Regarding to sarcoidosis, our patient had a high level of ACE, but the pathological examination was not suggestive of the disease and besides, it is well known that young people have higher levels of ACE without pathological significance [29]. Association with bacterial infection has been described previously, especially with Yersinia enterocolitica and Pasteurella multocida [9].…”
Section: Discussionmentioning
confidence: 46%